Paediatric reference ranges for faecal calprotectin: a UK study. (March 2017) - Davidson, Fiona; Lock, Robert J
Background: Faecal calprotectin has been shown to be a useful non-invasive marker for the diagnosis and monitoring of inflammatory bowel disease in children and adults. Although there are well-established reference ranges for the diagnosis of inflammatory bowel disease in adults, these have been less well studied in children. The objective was to establish reference ranges in our local population. Method: All faecal calprotectin results from 2011 to 2014 were retrospectively collated and grouped according to patient age. Probability plots were used to determine expected upper limit of normal for each age group, and Mann-Whitney test was used to determine statistical difference between groups. Results: Upper limit of normal for age groups 1–3.9 years, 4–17.9 years and 18 years plus were 77, 62 and 61  µ g/g, respectively. There was a significant difference ( P  = 0.0013) between the median calprotectin concentration for the age group 1–3.9 years ( n  = 87) and 4–17.9 years ( n  = 636) and between the age group 1–3.9 years and 18 years plus ( n  = 7953, P  = 0.0001), but there was no significant difference between the age groups 4–17.9 years and 18 years plus ( P  = 0.4206). Conclusions: In our local population, faecal calprotectin varies with age. Children aged 1–3.9 years had higher concentrations of faecal calprotectin than adults, but there was no significant difference in faecal calprotectin between older children and adults. This is in agreement with other published studies; however, the faecal calprotectin upper limit of normal calculated for children aged 1–3.9 years was lower than has been observed elsewhere.